Daily surface energy balance (SEB) and quality-controlled meteorological quantities measured at station GRL_KPC_U on the Greenland ice sheet - Maurice Van Tiggelen; Paul C J P Smeets; Carleen H Reijmer; Dirk van As; Jason E Box; Robert S Fausto; Shfaqat Abbas Khan; Eric Rignot; Michiel R van den Broeke (PANGAEA, 2024)
Daily averaged surface energy balance (SEB) components and meteorological quantities at 19 locations on the Greenland ice sheet. Three stations are located in the accumulation zone (S10, KAN_U and S21), while the other locations are in the ablation zone. Seven stations are part of the IMAU network , while the other stations are from the PROMICE network. The longest time series span between 2003 and 2023 (S5, S6 and S9, all located along the K-transect in West Greenland). The data contains modelled and measured turbulent heat fluxes, all four radiation components, daily melt energy, subsurface heat flux, air temperature, wind and humidity corrected at standard heights above the surface, height of the sensor, snow accumulation measured by a sonic height ranger, ice/snow ablation measured by a draw-wire, a pressure transducer depth assembly, or acoustic ranger mounted on a separate stake. Days with at least one missing sample are removed from the dataset.
In: Van Tiggelen, M et al. (2024): Daily surface energy balance (SEB) and quality-controlled meteorological quantities measured at 19 stations on the Greenland ice sheet (2003-2023) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.970127